2017
DOI: 10.1002/ppul.23785
|View full text |Cite
|
Sign up to set email alerts
|

Breathomics from exhaled volatile organic compounds in pediatric asthma

Abstract: Asthma is the most common chronic disease in children, and is characterized by airway inflammation, bronchial hyperresponsiveness, and airflow obstruction. Asthma diagnosis, phenotyping, and monitoring are still challenging with currently available methods, such as spirometry, F NO or sputum analysis. The analysis of volatile organic compounds (VOCs) in exhaled breath could be an interesting non-invasive approach, but has not yet reached clinical practice. This review describes the current status of breath ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 65 publications
1
81
1
4
Order By: Relevance
“…Although eNose provides breathprints that can be used to detect asthma and chronic obstructive pulmonary disease (COPD) [136], it does not identify individual VOC markers within a complex mixture. Ion mobility spectrometry (IMS) is a relatively sensitive method though it is destructive, may not be ideal for complex VOC mixtures and its long term reproducibility is yet to be demonstrated [137]. Currently, GC-MS is the gold standard for global profiling of exhaled VOCs related to abnormal metabolism and extrapolated to cancers, diabetes etc.…”
Section: Sers In Breath Analysismentioning
confidence: 99%
“…Although eNose provides breathprints that can be used to detect asthma and chronic obstructive pulmonary disease (COPD) [136], it does not identify individual VOC markers within a complex mixture. Ion mobility spectrometry (IMS) is a relatively sensitive method though it is destructive, may not be ideal for complex VOC mixtures and its long term reproducibility is yet to be demonstrated [137]. Currently, GC-MS is the gold standard for global profiling of exhaled VOCs related to abnormal metabolism and extrapolated to cancers, diabetes etc.…”
Section: Sers In Breath Analysismentioning
confidence: 99%
“…Additionally, since the lung microbiome is difficult to sample, the nasal, the salivary, or even the gut microbiome could be examined as non-invasive alternatives to the lung microbiome due to the relationship between the upper and the lower airways [84,85] and the gut-lung axis [72]. Although proteomics and breathomics have been used for profiling of asthma [60,86,87], during the reviewed period, no study has been focused on treatment response in children with asthma. Breathomics and sputum or salivary proteomics could be straightforwardly applicable in the clinics in terms of non-invasiveness, which provides an outstanding benefit in the management of pediatric asthma.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput analytical techniques, such as mass spectrophotometry, nuclear magnetic resonance, or spectroscopic methods, allow the characterizing of metabolites in invasive samples like blood and in non-invasive ones such as exhaled air (breathomics). This recent omic has been successfully applied for the profiling of asthma [59][60][61] and may contribute to understanding asthma treatment response.…”
Section: Metabolomicsmentioning
confidence: 99%
“…It would seem then that the review by Neerincx et al succeeded in capturing the majority of relevant literature; the additionally identified study adds little to their findings. The abstracts identified by our search present results largely relating to the ability of VOCs to differentiate between states of disease control, the results of which were conflicting.…”
mentioning
confidence: 99%
“…I read with interest the engaging review by Neerincx et al—Breathomics from exhaled volatile organic compounds (VOCs) in pediatric asthma. The results are encouraging suggesting good predictive accuracy for VOC profiles in asthma diagnosis.…”
mentioning
confidence: 99%